Optimising swaps to reduce the salt content of food purchases in a virtual online supermarket: A randomised controlled trial - Payne Riches, S; Aveyard, P; Piernas, C; Rayner, M; Jebb, S (Elsevier, 2018)
Background Offering consumers the opportunity to swap to lower-salt foods while shopping has potential to reduce salt intake. Offering a wider range of alternatives which are much lower in salt could increase the magnitude of salt reduction gained but may interfere with consumers’ engagement and willingness to accept swaps. Objectives To compare the salt reduction from offering swaps to a similar product but with minimally less salt to offering swaps with a substantial salt reduction including a range of alternative foods. Methods In an experimental, randomised trial conducted in a virtual online supermarket, participants with high blood pressure were asked to buy 12 items of food. One group was offered similar alternatives with 5–20% less salt (LS swaps); and the other group was offered these LS swaps and alternatives with>20% less salt (MLS swaps). The primary outcome was the change in salt density of the shopping basket (g/100g) from initially selected items, to the final items chosen. Results 947 participants completed the task and were included in the analysis. There was a significant reduction in salt content of the final selected shopping basket in both groups; with a significantly greater reduction in the group offered LS + MLS swaps (−0.09g/100g, 95% C.I. −0.10, −0.07; p < 0.001). The proportion of swaps accepted was the same in both groups and the mean salt reduction per swap accepted in the group offered LS + MLS swaps was more than double that of the group offered LS swaps alone. 30% of MLS swaps accepted were from a different food subcategory. Conclusions Offering alternative products with a large reduction in salt, including potentially dissimilar products, does not decrease acceptability and leads to significantly greater reductions in the salt content of the shopping basket.